Kewenangan Hakim dalam Memutus Perkara Tindak Pidana Anak Pelaku Pengeroyokan yang Menyebabkan Kematian pada Putusan No. 5/Pid.Sus-Anak /2021 /Pn. Sim. - Sormin, Anggreana Elisabeth Roria; Zulyadi, Rizkan; Siregar, Taufik (Mahesa Research Center, 2023)
This study raises the formulation of the problem, namely (1) How to regulate the authority of judges according to laws and regulations, (2) How are the factors that influence the crime of beatings that cause death by children, (3) What are the basic considerations of judges at the Simalungun District Court in decide on a criminal case in case no. 5/Pid-Child/2021/PN. Sim. The research method uses a normative juridical method by analyzing the laws and regulations and conceptually by analyzing descriptive data analysis. The results of this study indicate that the rule of law regarding the authority of judges according to the legislation, namely Law no. 48 of 2009 concerning judicial power and Joint Regulation of the Constitutional Court and the Judicial Commission of the Republic of Indonesia Number 047/KMA/SKB/IV/2009-02/SKB/P.KY/IV/2009 concerning guidelines for enforcing codes of ethics and guidelines for judge behavior, the factors that influence the crime of beatings that cause death by children, and the Basis for Consideration of the Judges of the Simalungun District Court in Deciding the Criminal Case of Beating Perpetrated by Children in the Decision on Criminal Case No. 5 Pid.Sus-Child/2021/PN. Sim.Â The judge considering that the juvenile justice system must prioritize the Restorative Justice approach, and must strive for diversion with the aim of achieving peace between victims and children, resolving child cases outside the judicial process, preventing children from being deprived of independence, encouraging the community to participate and instilling a sense of responsibility to children. Suggestions from this thesis are the imposition of criminal sanctions for children, judges should consider prison sentences for children, this is to avoid children from negative influences in the prison environment.